The role of radiotherapy in small cell lung cancer: a new paradigm for the radiation oncologist - Borghetti, Paolo; Ramella, Sara; Ricardi, Umberto (Frontiers in Oncology, 2025)
Small cell lung cancer (SCLC) is an aggressive tumor that presents in most cases as a metastatic disease. The prognosis is poor, but the advent of immunotherapy has rekindled hopes for outcomes. Radiotherapy plays a crucial role in this oncological scenario, and there are still many open questions on the correct application of radiotherapy and its integration with chemotherapy and immunotherapy. These issues are of great interest to the oncology community; among these, in particular, there are the choice of optimal fractionation and total dose for thoracic radiotherapy in limited SCLC and its biological implications, the role of prophylactic cranial irradiation and thoracic consolidation in the context of modern treatments with chemoimmunotherapy in extensive SCLC, the role and indications of stereotactic radiotherapy in oligometastatic scenario and finally the complex clinical and multidisciplinary management of SCLC. This perspective article aims to describe the strengths and limitations of the role of radiotherapy in SCLC, highlighting the critical role of radiotherapy and the radiation oncologist, with the need to implement specific knowledge and skills on SCLC.